INFLUENCING OF NEW REHABILITATION "REOMANNISOL" ON LIPID PEROXIDATION AND ANTIOXIDANT SYSTEM IN EXPERIMENTAL HEMOLITIC ANEMIA - Sh.M, Fazilova; Ya, Karimov Kh.; D.S, Matkarimova; M.T., Yusupova (International Journal of Psychosocial Rehabilitation, 2020)
Goal of the research: to conduct a comparative assessment of the effectiveness of the new Reomannisol blood substitute on the state of lipid peroxidation and antioxidant system indicators in hemolytic anemia in the experiment. Materials and methods. On white laboratory rats (n = 120, average body weight 178.5 ± 5.8 g.), A model of hemolytic anemia was reproduced by a single intraperitoneal administration of a 2% solution of phenylhydrazine at a dose of 50 mg / kg of animal weight. In laboratory animals, the parameters of antioxidant protection and lipid components in the blood were studied. Results. In a comparative study of the new Reomannisol blood substitute, it was proved that it restores the state of lipid peroxidation and the activity of AOS enzymes in hemolytic anemia, more effective than other analogues and can be used in medical practice, in pathological conditions associated with hypoxic conditions.